Instrumental Competence in Translation and Interpreting Curricula in Spain: pre-EHEA vs. EHEA Bachelor's Degrees. - Plaza-Lara, Cristina (Universidad de Helsinki, 2016)
The implementation of the European Higher Education Area has made it necessary for universities to adapt to market requirements. The introduction of new technologies in the translation process and changes in the kinds of texts to be translated require universities to increase the number of subjects in which instrumental competence is essential. These subjects are mainly (but are not limited to) computer science, documentation, terminology and audiovisual translation. To enable the drawing of conclusions regarding the changes introduced by the Bologna Process, two comparative tables will be presented that allow the reader to review the changes made in recent years to Translation and Interpreting studies at Spanish universities with regard to instrumental competence. Some of these conclusions are summarised and our own proposal regarding the distribution of this content in translation curricula is presented.
Keywords: Traducción - Programas de estudio; Traducción - Innovaciones tecnológicas; Traducción - Estudio y enseñanza superior; PRE-EHEA bachelor degree; EHEA bachelor degree; Instrumental subcompetence; Translation and interpreting curricula; Computer tools in translation studies